The DevOps handbook how to create world-class agility, reliability, & security in technology organizations - Kim, Gene; Humble, Jez; Debois, Patrick; Willis, John (IT Revolution Press, 2021)
This award-winning and bestselling business handbook for digital transformation is now fully updated and expanded with the latest research and new case studies! Over the last five years, The DevOps Handbook has been the definitive guide for taking the successes laid out in the bestselling The Phoenix Project and applying them in any organization. Now, with this fully updated and expanded edition, it's time to take DevOps out of the IT department and apply it across the full business. Technology is now at the core of every company, no matter the business model or product.
Keywords: Agile software development; Information technology -- Management; Computer software -- Development; Corporate culture; Industrial management; Méthodes agiles (Développement de logiciels); Technologie de l'information; Gestion; Culture organisationnelle; Gestion d'entreprise; Information technology; Management; Computer software; Development